2019
DOI: 10.14267/turbull.2019v19n3.1
|View full text |Cite
|
Sign up to set email alerts
|

A fesztiválélmény megjelenése a közösségi médiában: a Sziget Fesztivál példája

Abstract: A tanulmány célja, hogy bemutassa egy nagy hazai fesztivál által generált fogyasztói élmény di­menzióit. Az áttekintő fesztiválkörkép és a fesztiválok szerepének elméleti bemutatása után, affek­tív és kognitív értékdimenziók mentén megvizsgálja a Sziget Fesztivál, mint vezető kulturális tu­risztikai termék látogatói számára élményt generáló tényezőket, különös tekintettel az affektív és a kognitív értékdimenziókra, amelyeket tanulmányunkban az élményteremtés pilléreinek nevezünk. A vizsgálatot a 2016-os Sziget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Of the three sections of photos, the category on events and festivals was the section with the least respondents selecting the photo we marked (where fewer people are included) (28.6%). Previously published studies have shown that even in the case of mass events, such as festivals and other large events, crowds and congestion are disturbing for participants and are usually voiced by visitors (Hinek -Kulcsár, 2019;Formádi et al, 2019;Kiss -Hinek, 2020). However, it is undeniable that visitors attending festivals and larger events are usually aware of the fact that the program of their choice is likely to be crowded, and thus less likely to view this phenomenon as an unexpected problem.…”
Section: Heat Map Visualisationmentioning
confidence: 99%
“…Of the three sections of photos, the category on events and festivals was the section with the least respondents selecting the photo we marked (where fewer people are included) (28.6%). Previously published studies have shown that even in the case of mass events, such as festivals and other large events, crowds and congestion are disturbing for participants and are usually voiced by visitors (Hinek -Kulcsár, 2019;Formádi et al, 2019;Kiss -Hinek, 2020). However, it is undeniable that visitors attending festivals and larger events are usually aware of the fact that the program of their choice is likely to be crowded, and thus less likely to view this phenomenon as an unexpected problem.…”
Section: Heat Map Visualisationmentioning
confidence: 99%
“…Previous research examined the elements of festival experiences as they appear in eWOM through manual analysis. As an immediate antecedent to the present research, Hinek and Kulcsár (2019) investigated the experiential dimensions of the Sziget Festival in this way. In their research they conducted a qualitative text analysis of guest reviews on the Sziget Festival Official website.…”
Section: Introductionmentioning
confidence: 99%